The Effect of Problem Based Learning Model on Students’ Learning Outcomes and Social Emotional Skills in the Topic of Virus - Natasya Ulfa; Hafnati Rahmatan; Safrida Safrida; Andi Ulfa Tenri Pada; Muhibbuddin Muhibbuddin; Nor Asniza Ishak (Universitas Syiah Kuala, in collaboration with the Perkumpulan Pendidik IPA Indonesia (PPII), (MoU), 2025)
The demands of 21st-century education emphasize the importance of social emotional skills (SES) and learning outcomes as essential provisions for students to face global challenges. This study aims to analyze the effect of implementing the problem-based learning (PBL) model on students’ social-emotional skills and learning outcomes in the topic of viruses, as well as to examine the relationship between these two variables. The research employed a quasi-experimental approach with a pre-test–post-test non-equivalent control group design. SES data were collected using a questionnaire developed based on the collaborative for academic, social, and emotional learning (CASEL) competencies, while learning outcomes were obtained through pre-test and post-test assessments. Data analysis was carried out using an independent sample t-test and Pearson correlation at a 0.05 significance level. The findings reveal that the SES of students in the experimental class were higher than those in the control class after the implementation of PBL. Students’ learning outcomes also improved significantly, as indicated by higher post-test scores and N-gain in the experimental class compared to the control class. Furthermore, although the correlation between SES and learning outcomes was weak, the results still indicate a positive relationship, suggesting that improvements in students’ SES are accompanied by increases in their academic performance. These findings conclude that the implementation of the PBL model remains effective in enhancing both SES and learning outcomes, and is highly relevant to the demands of 21st-century learning.